Insights into the mechanism and kinetics of dissolution of aluminoborosilicate glasses in acidic media: Impact of high ionic field strength cations - Qin, Qianhui; Stone-Weiss, Nicholas; Zhao, Tongyao; Mukherjee, Pinaki; Ren, Jinjun; Mauro, John C.; Goel, Ashutosh (Acta materialia, 2023)
Achieving thinner and higher performance display/substrate glasses and transparent glass-ceramics with tunable properties requires a precise control of acid-etching process, thus necessitating a comprehensive understanding of glass composition–structure–dissolution behavior relationships in acidic medium. Unfortunately, the literature on this subject has been focused only on a narrow set of glass chemistries. Therefore, consensus on the mechanisms that govern the acidic dissolution of multicomponent silicate glasses over a broad compositional space is still lacking. The present work employs a suite of state-of-the-art spectroscopic techniques, including 1D and 2D NMR, TEM-EELS, ICP-OES, and XPS, to provide an insight into the mechanism and kinetics of corrosion of alkali/alkaline-earth aluminoborosilicate glasses (comprising high field strength cations – HFSCs, i.e., La3+, Ti4+, Zr4+ and Nb5+) in acidic media (HCl; pH = 2). Incorporating the HFSCs into the glasses induces significant structural changes in their network, thus, impacting the forward rate dissolution kinetics. Based on the results, we hypothesize that the glasses dissolve at pH = 2 through an ‘interfacial dissolution – re-precipitation mechanism (IDPM)’ and ‘in-situ recondensation’ coupled pattern, wherein the IDPM results in a Si-rich alteration layer, followed by local recondensation occurring due to limited kinetics near the interfacial solution between the uncorroded glass surface and the outer alteration layer. [Display omitted]